2015
DOI: 10.1002/cssc.201501259
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization as a Strategy to Combine Epoxidized Linseed Oil and Furfuryl Alcohol: The Design of a Fully Bio‐Based Thermoset

Abstract: Epoxidized linseed oil and furfuryl alcohol are bio-sourced monomers known for their high-potential applications in materials science. In this work, we propose the association of these monomers through copolymerization reactions with the target to design fully bio-based thermosets. Herein, investigations on cationic polymerization reactivity have been explored using differential scanning calorimetry. The obtained structures have been confirmed by IR spectroscopy and 2 D NMR spectroscopy, which revealed the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 48 publications
3
55
0
Order By: Relevance
“…Therefore, the α relaxation peak of the furfurylated wood shifted to a lower temperature due to the effect of PFA. In addition, the amplitude of the tan δ peak was smaller than control, which manifested in increased brittleness of the furfurylated wood . The damping peak in DL‐FA sample showed a decreased magnitude of tan δ compared to the control and furfurylated sample, attributed to the increased interaction between the PFA and wood components that allowed for greater stress transfer at the interface .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, the α relaxation peak of the furfurylated wood shifted to a lower temperature due to the effect of PFA. In addition, the amplitude of the tan δ peak was smaller than control, which manifested in increased brittleness of the furfurylated wood . The damping peak in DL‐FA sample showed a decreased magnitude of tan δ compared to the control and furfurylated sample, attributed to the increased interaction between the PFA and wood components that allowed for greater stress transfer at the interface .…”
Section: Resultsmentioning
confidence: 88%
“…For the control sample, the α relaxation at about 237°C is related to the micro‐Brownian motions of the wood components in the amorphous region while the β relaxation process at about 70°C is a hemicellulose glass transition peak . There are no studies on the dynamic mechanical properties of furfurylated wood, but it was reported that PFA exhibited a main relaxation peak at about 145°C, which is typical for highly cross‐linked thermosets . Therefore, the α relaxation peak of the furfurylated wood shifted to a lower temperature due to the effect of PFA.…”
Section: Resultsmentioning
confidence: 99%
“…This was recently exemplifiedf or furanicp olyesterso btained from citric acid, which were able to self-cross-linki nto elastomeric thermosets via furan ring-opening. [12] The combinationo fP FA with other biobased reagents, such as epoxidized vegetable oils, [13,14] is also possible to tailor its cross-link density and, by extension, its physicalproperties. [9] The first step consists of oligomer formation by FA polycondensation.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In order to further improve chemical, thermal and mechanical properties of epoxy resins, the presence of signicant content of aromatic moieties is required. In this frame, lignin derivatives appear to be the natural substitutes of BPA.…”
mentioning
confidence: 99%